Acute exposure to an organochlorine pesticide alters locomotor behavior and cardiac function in the freshwater invertebrate Daphnia magna. Issue 2 (4th March 2021) - Duong, Thanh-Binh; Odhiambo, B.K; Oldham, Davis; Hoffman, Mary; Frankel, Tyler Edward
ABSTRACT: In this study, the acute impacts of aqueous methoxychlor exposure on the viability, locomotive behavior, and heartrate of Daphnia magna was assessed. Adults were exposed to 0 (ethanol control), 1, 2.5, 5, or 10 µg/L of methoxychlor for 48 hr using a static exposure assay. After 24 hr mobility was quantified using automated behavioral analysis software and differences in mortality and heartrate assessed after 24 and 48 hr. Exposure caused an increase in mortality after 48 hr, with effects seen in as little as 24 hr in the 10 µg/L treatment. Decreases in speed, total distance traveled, and frozen events were observed after 24 hr. Heartrate in the 10 µg/L treatment was depressed after 24 hr, with decreases in the 2.5 and 5 µg/L treatments observed after 48 hr. These results provide an expanded understanding of the impacts of a well-established legacy organochlorine pesticide on a model invertebrate.